A prospective study on the natural course of low‐grade squamous intraepithelial lesions and the presence of HPV16 E2‐, E6‐ and E7‐specific T‐cell responses - Woo, Yin Ling; van den Hende, Muriel; Sterling, Jane C.; Coleman, Nicholas; Crawford, Robin A.F.; Kwappenberg, Kitty M.C.; Stanley, Margaret A.; van der Burg, Sjoerd H. (International journal of cancer, 2010)
This study investigates the clinical course of low grade squamous intraepithelial lesions (LSIL), HPV status and HPV16‐specific immune response in a large prospective study of 125 women with LSIL followed cytologically, virologically and histologically. Women with low‐grade abnormal smears were recruited and followed‐up for one year. Colposcopy, cervical biopsy for histology and brushings for HPV typing was performed at recruitment, 6 months (no biopsy) and upon completion of the study at one year. HPV16‐specific T‐cell responses were analysed by interferon‐γ ELISPOT at entry, 6 and 12 months. Infection with multiple HPV types was detected in 70% of all patients, HPV16 was found in 42% of the patients. LSIL lesions progressed to HSIL in 24%, persisted in 60% and regressed to normal in 16% of the patients. No difference was observed in the clearance rate of infections with single or multiple HPV types among the groups with a different histological outcome. HPV16‐specific type 1 T‐cell responses were detected in only half of the patients with an HPV16+ LSIL, and predominantly reactive to HPV16 E2 and E6. Interestingly, the presence of HPV16 E2‐specific T‐cell responses correlated with absence of progression of HPV16+ lesions (p = 0.005) while the detection of HPV16 E6 specific reactivity was associated with persistence (p = 0.05). This large prospective study showed that the majority of LSIL persisted or progressed within the first year.This was paralleled by immune failure as most of the patients with an HPV16+ LSIL failed to react to peptides of HPV16 E2, E6 or E7.